Analisis Harga Wajar Saham dengan Metode Discounted Cash Flow PT Bank Tabungan Negara Tbk periode 2013-2017 - Nurhadiman, Redi; Septariani, Desy (Sosio e-Kons, 2019)
The purpose of the research is to analyze and find out the fair price of the shares of PT Bank Tabungan Negara, Tbk for the period 2013-2017. The research method use quantitative descriptive methods with analyze discounted cash flow methods with proxy earning per share, dividen pay out ratio, price earning ratio dan required rate of return. The result research in 2013, 2014 and 2016 stock prices were undervalued while in 2015 and 2017 the stock prices were overvalued. Then based on the analysis using the graph of stock price movements of PT Bank Tabungan Negara, Tbk for the period 2013-2017, the results show that in 2013 and 2014 the share price of PT Bank Tabungan Negara, Tbk was almost close to its fair price, while in 2015, 2016 and 2017 the stock price PT Bank Tabungan Negara, Tbk has reached and exceeded its fair price.